Adaptive Resource Allocation Algorithm in Wireless Access Network - Zhanjun Liu; Yue Shen; Zhonghua Yu; Fengxie Qin; Qianbin Chen (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
Wireless network state varies with the surrounding environment, however, the existing resource allocation algorithm cannot adapt to the varying network state, which results to the underutilization of frequency and power resource. Therefore, in this paper, we propose an adaptive resource allocation algorithm which can efficiently adapt to the varying network state by building an optimal mathematical model and then changing the weighted value of the objective function. Furthermore, the optimal allocation of subcarrier and power is derived by using the Lagrange dual decomposition and the subgradient method. Simulation results show that the proposed algorithm can adaptively allocate the resource to the users according to the varying user density which represents the network state.